Karasteristik Serbuk Buah Mangrove Rhizophora sp. - Wulandari, Sri; Karmila, Ziana; Widayati Putri, Tri; Khairiyah, Zul (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2023)
Mangroves have various roles for human life, one of which is as an alternative food ingredient, namely coffee raw material. Mangrove propagules, especially the fruit, can be processed and produce powders that can be brewed like coffee in general so this study aims to analyze the characteristics of mangrove fruit powder by calculating ash content, water content, caffeine, followed by sensory and hedonic testing of Rhizophora sp. This study used a laboratory-scale quantitative method followed by panelists' assessment of two different samples. Sample one is Rhizophora sp. mangrove fruit powder, while sample two is a mixture of Rhizophora sp. mangrove fruit powder with the addition of Arabica coffee beans. The test results of ash content, moisture content, caffeine, sensory, and hedonic testing respectively showed values of 2.48 and 1.49; 2.94 and 3.03; 1.36 and 0.92; 23.3 and 25.1; and 27.1 and 28.3. So it can be concluded that the water content and ash content of mangrove fruit powder with the addition of arabica coffee beans are higher than mangrove fruit powder. Although the caffeine content of mangrove fruit powder is higher than those that get additional arabica coffee. Mangrove fruit powder with the addition of Arabica coffee beans has a higher value in sensory and hedonic testing, panellists prefer and feel more satisfied when consuming mangrove fruit powder with the addition of Arabica coffee.